2016
DOI: 10.5423/ppj.ft.08.2016.0165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Tomato yellow leaf curl virus C4 Protein-Interacting Host Proteins in Healthy and Infected Tomato Tissues

Abstract: Tomato yellow leaf curl virus (TYLCV), a member of the genus Begomovirus, is one of the most important viruses of cultivated tomatoes worldwide, mainly causing yellowing and curling of leaves with stunting in plants. TYLCV causes severe problems in sub-tropical and tropical countries, as well as in Korea. However, the mechanism of TYLCV infection remains unclear, although the function of each viral component has been identified. TYLCV C4 codes for a small protein involved in various cellular functions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…They are also indicated to play a role in plant immune responses. These 14-3-3 proteins were identified as putative key regulators of the response to Tomato yellow leaf curl virus infecting tomato plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are also indicated to play a role in plant immune responses. These 14-3-3 proteins were identified as putative key regulators of the response to Tomato yellow leaf curl virus infecting tomato plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, that the 26S proteasome system participates in degradation of TMV MP, specific inhibition experiments, however, have indicated that TMV infection rather benefits from this process [66]. Plant aspartate protease Asp1 interacted with the begomoviral C4 protein in the yeast two-hybrid system [67], which may indicate its activity and intervention during viral infection. The NRT1/PTR family proteins (nitrate/peptide transporters) take part in abscisic acid transport in plant tissues [68].…”
Section: Up-regulation By CMV Infectionmentioning
confidence: 99%
“…TYLCSV C2 interacts with the COP9 subunit of the signalosome (CSN), a complex involved in the regulation of the ubiquitination, preventing tagging the virus for destruction ( Lozano-Durân et al, 2011 ). TYLCV C4 protein interacts with tomato plant defense proteins ( Kim et al, 2016 ).…”
Section: Tylcv Interactions With Plant Host and Insect Vector Heat Shmentioning
confidence: 99%